Transforming smallholder irrigation into profitable and self-sustaining systems in southern Africa - Bjornlund, Henning; Parry, K.; Pittock, J.; Stirzaker, R.; Rooyen, Andre F. van; Moyo, M.; Mdemu, M.; Sousa, W. de; Cheveia, E.; Munguambe, Paiva; Kimaro, E.; Kissoly, L.; et al. (2018)
Small-scale communal irrigation schemes in Africa have not realised returns on investment. Critical to this failure is that funders, designers and managers of these schemes have not recognized them as complex socio-ecological systems with a diversity of constraints. These schemes are often under-performing and characterized by a subsistence orientation, which is compounded by poor market integration, low capacity to invest in crop production, low yields, difficulties paying for water, or lack of willingness to participate in system maintenance. The end result is unsustainable utilization of resources, failed infrastructure, inefficient use of water and land and increased conflict over access to these resources. Conventional irrigation scheme development has focused on ‘hard’ technologies to improve the functionality and efficiency of infrastructure and/or irrigation application technologies. However, hard technology improvements on their own have failed to deliver sustainable schemes and improve the livelihoods of irrigation farmers (Inocencio et al., 2007): broken and decaying infrastructure is just one element of an underperforming system. While technologies that are more efficient may help improve yield, they will not necessarily improve profitability. A great many irrigation schemes are trapped in a negative cycle of infrastructure provision, unprofitable farming, lack of investment in maintenance, infrastructure degradation leading to donors subsidizing infrastructure rehabilitation (Pittock & Stirzaker, 2014; Bjornlund et al., 2017).